2002
DOI: 10.1159/000064927
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Proton Magnetic Resonance Spectroscopy Studies in Dementia and Parkinson’s Disease

Abstract: We reviewed the literature of proton magnetic resonance spectroscopy (MRS) in dementia and Parkinson’s disease (PD) and quantitatively compared the reported values of the markers N-acetyl aspartate (NAA), choline, and myo-Inositol between control and disease groups. We analysed a total of 27 reports in dementia. Combining the quantitative data from these showed a relative decrease of 15% in NAA level in the temporal lobe tissue in patients with Alzheimer’s disease (AD) compared with controls. The rest of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
2
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 78 publications
(111 reference statements)
4
97
2
1
Order By: Relevance
“…Its use as a diagnostic test for PD has been hampered by the inability of previous tests to precisely localize it to the SNpc, a necessary prerequisite because of the exacting relationship of NAA to neuronal injury and the requirement for high-field MRSI to ensure precise quantitative measurements (Clarke et al, 1997;Cruz et al, 1997;Federico et al, 1997;Brooks, 2000;Clarke and Lowry, 2000;Firbank et al, 2002;Baik et al, 2003). Nevertheless, a number of advantages to NAA measurements are evident, including its exclusive relationship to synthesis in neuronal mitochondria and reduction in mitochondrial dysfunction (Clark, 1998;Signoretti et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Its use as a diagnostic test for PD has been hampered by the inability of previous tests to precisely localize it to the SNpc, a necessary prerequisite because of the exacting relationship of NAA to neuronal injury and the requirement for high-field MRSI to ensure precise quantitative measurements (Clarke et al, 1997;Cruz et al, 1997;Federico et al, 1997;Brooks, 2000;Clarke and Lowry, 2000;Firbank et al, 2002;Baik et al, 2003). Nevertheless, a number of advantages to NAA measurements are evident, including its exclusive relationship to synthesis in neuronal mitochondria and reduction in mitochondrial dysfunction (Clark, 1998;Signoretti et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The degree of cognitive impairment was found to be well correlated with the degree of NAA decrease [90]. In addition, several studies found MRS also useful in differentiating AD from other forms of dementia, eg, vascular dementia, fronto-temporal lobe dementia [85,86,[91][92][93].…”
Section: Other Potential Neuroimaging Biomarkersmentioning
confidence: 94%
“…Proton magnetic resonance spectroscopy of the striatum has provided variable results in PD itself, but this technique may be useful for differentiating between PD and atypical parkinsonian syndromes, such as multiple system atrophy or progressive supranuclear palsy [13][14][15][16], and there may also be changes in the posterior cingulate [17] and presupplementary motor area cortex [18]. Phosphorus spectroscopy may also reveal changes that appear to differ between PD and multiple system atrophy [19,20].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%